URGENSI BERAGAMA DI ERA PERKEMBANGAN IPTEK (ANALISIS PEMIKIRAN M. NURUDDIN DALAM VIDEO YOUTUBE KAIFA CHANNEL) - Reo Chandrika; Jeni Lovita (Jurnal Humaniora & Sosial Sains, 2025)
This research aims to analyze M. Nuruddin's views regarding the role of religion in the context of current advances in science and technology (IPTEK) in his video recording on the Kaifa YouTube channel with the title "Do we still need religion?" The video has been watched by approximately three thousand viewers. The author uses a literature study approach, this research examines various written works and articles related to M. Nuruddin's thoughts regarding the relationship between religion and science and technology. The results of the analysis show that M. Nuruddin emphasizes the importance of religion as a moral foundation in facing the challenges of the digital era. He argued that religious values can be a guide for individuals in controlling and organizing their daily lives. Thus, religion not only functions as a balance in the digital era, but also as a driving force for creating technological innovations that are beneficial to society.